(3QSGdI aj GdJUhas - (3YHO Gddg Hf CMeO Hf eMeO Hf bOGeI GdLeGYjdj GdebOSj Ke GdOeTbj GdMfHdj, ehab GdOjf GHf bOGeI , J (B620 (3gs
(3ChdgG (B:s
(3CeG HYO abO SCdfi HYV ENhGfi GdUGdMjf Cf CcJH dg hUjI CLHJg Edi eSFdJg QLG KhGH bVG MGLJg s
(3BNQgG (B:s
(3Ef gPG GdcaQ hGdYPGH de jcf HSHH GdEYJbGO Ch GdLgd hGdHZV ddOjf Ch eMHI GdcaQ hEfeG SHHg Ef dg ai Pdc MXkG ef MXhX GdOfjG aGKQg Ydi GdOjf hGddg SHMGfg hJYGdi GYde GdMeO ddg hMOg hUdi Gddg Ydi eMeO hSde s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B67 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B30 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B459s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs